Sucrose synthase gene SUS3 could enhance cold tolerance in tomato - Li, Shouming; Wang, Ying; Liu, Yuanyuan; Liu, Changhao; Xu, Wei; Lu, Yongen; Ye, Zhibiao (Frontiers in Plant Science, 2024)
Tomatoes are susceptible to damage from cold temperatures at all stages of growth. Therefore, it is important to identify genetic resources and genes that can enhance tomato's ability to tolerate cold. In this study, a population of 223 tomato accessions was used to identify the sensitivity or tolerance of plants to cold stress. Transcriptome analysis of these accessions revealed that SUS3 , a member of sucrose synthase gene family, was induced by cold stress. We further investigated the role of SUS3 in cold stress by overexpression (OE) and RNA interference (RNAi). Compared with the wild type, SUS3-OE lines accumulated less MDA and electrolyte leakage, more proline and soluble sugar , maintained higher activities of SOD and CAT, reduced superoxide radicals, and suffered less membrane damage under cold. Thus, our findings indicate that SUS3 plays a crucial role in the response to cold stress. This study indicate that SUS3 may serve as a direct target for genetic engineering and improvement projects, which aim to augment the cold tolerance of tomato crops.